ChemInform Abstract: Poly‐NHC Complexes of Transition Metals: Recent Applications and New Trends. Issue 44 (13th October 2016) - Biffis, Andrea; Baron, Marco; Tubaro, Cristina
Abstract: Review: 296 refs.